Characterization and review of MTHFD1 deficiency: four new patients, cellular delineation and response to folic and folinic acid treatment. Issue 5 (30th January 2015) - Burda, P.; Kuster, A.; Hjalmarson, O.; Suormala, T.; Bürer, C.; Lutz, S.; Roussey, G.; Christa, L.; Asin‐Cayuela, J.; Kollberg, G.; Andersson, B. A.; Watkins, D.; et al.
Abstract: In the folate cycle MTHFD1, encoded by MTHFD1, is a trifunctional enzyme containing 5, 10‐methylenetetrahydrofolate dehydrogenase, 5, 10‐methenyltetrahydrofolate cyclohydrolase and 10‐formyltetrahydrofolate synthetase activity. To date, only one patient with MTHFD1 deficiency, presenting with hyperhomocysteinemia, megaloblastic anaemia, hemolytic uremic syndrome (HUS) and severe combined immunodeficiency, has been identified (Watkins et al J Med Genet 48:590–2, 2011). We now describe four additional patients from two different families. The second patient presented with hyperhomocysteinemia, megaloblastic anaemia, HUS, microangiopathy and retinopathy; all except the retinopathy resolved after treatment with hydroxocobalamin, betaine and folinic acid. The third patient developed megaloblastic anaemia, infection, autoimmune disease and moderate liver fibrosis but not hyperhomocysteinemia, and was successfully treated with a regime that included and was eventually reduced to folic acid. The other two, elder siblings of the third patient, died at 9 weeks of age with megaloblastic anaemia, infection and severe acidosis and had MTFHD1 deficiency diagnosed retrospectively. We identified a missense mutation (c.806C > T, p.Thr296Ile) and a splice site mutation (c.1674G > A) leading to exon skipping in the second patient, while the other three harboured a missense mutation (c.146C > T, p.Ser49Phe) and a premature stop mutation (c.673G > T, p.Glu225*), all of which were novel. Patient fibroblast studies revealed severely reduced methionine formation from [ 14 C]‐formate, which did not increase in cobalamin supplemented culture medium but was responsive to folic and folinic acid. These additional cases increase the clinical spectrum of this intriguing defect, provide in vitro evidence of disturbed methionine synthesis and substantiate the effectiveness of folic or folinic acid treatment.